Development of Mercury-Free Far-UVC Light Source Using Luminous Array Film Technology and Its Germicidal Effects - Koichi Shinoda; Kazuaki Mawatari; Thi Kim Ngan Bui; Yasuko Kadomura-Ishikawa; Takashi Uebanso; Hitoshi Hirakawa; Kenji Awamoto; Masayuki Wakitani; Tsutae Shinoda; Akira Takahashi (IEEE Access)
Far-UVC has emerged as a promising alternative for ultraviolet germicidal irradiation (UVGI). We developed a novel far-UVC light source using Luminous Array Film (LAFi), which excites phosphors by plasma discharge in a neon-xenon gas mixture within a glass tube. An optimal phosphor composition was determined, comprising aluminum phosphate, lutetium phosphate, and scandium. The plasma light module (PLM228) emits far-UVC radiation with a peak wavelength of 228 nm. Improvements in emission intensity and ozone generation suppression were achieved by modifying the glass materials. Escherichia coli, methicillin-resistant and methicillin-sensitive Staphylococcus aureus, and influenza A virus were inactivated by approximately 99.9% (−3 log10) upon exposure to 3 mJ/cm2 irradiation using PLM228. The bactericidal and virucidal effects of PLM228 surpassed those of other UV and far-UVC devices. PLM228 demonstrates significant potential as a mercury-free alternative UV germicidal light source.